GE_GERICHTE C/26458/2014 vom 3. Mai 2018 - GE Cour de justice (2018)
NATURE JURIDIQUE ; EMPLOYÉ DE MAISON ; RÉSILIATION IMMÉDIATE ; TAUX D'OCCUPATION(TRAVAIL) ; FARDEAU DE LA PREUVE | CPC.317; CPC.316; CO.319; CO.337.letc; CO.337